Connecting through e-portfolio practice: Trust, relationships and expertise - D'Souza, Ingrid; Sapsed, Carmen; Volcic, Zala (Journal of University Teaching and Learning Practice, 2025)
Trust, relationships, expertise, and connections are essential components in the practice of authentic, programmatic e-portfolio practice. The behind-the-scenes educational practices of Educational Designers, a Program Director and Academics in the implementation and design of student-curated, authentic programmatic assessments is definitely not well researched. Thus, our paper introduces, analyses, and reflects on the different aspects and layers of e-portfolio implementation into a bachelor degree. Through our personal lenses, we uncover some of the key lessons we have learned during this unique opportunity. The paper is not about addressing the technological implementation of the e-portfolio platform, nor simply pedagogical underpinnings; instead, we focus on the convergence of pedagogical practice relationships which are essential during the process of emerging, connecting and sustaining e-portfolios through an ongoing community of practice, within the learning lifecycle.